Effectiveness of the Nareswari Method (Breathing, Relaxation, and Coloring) on Reducing Anxiety Levels in Postpartum Mothers" - Alfadefi Khalifatunnisak; Atik Farokah; Anna Septina Andarini (PROFESSIONAL HEALTH JOURNAL, 2025)
Background: The postpartum period is a period of adaptation that is quite difficult for a mother. Various complaints can arise during the postpartum period, both physical and psychological complaints. Postpartum hormonal changes and adaptation to a new role as a mother often cause mothers to experience changes in mood, and become easily sad and sensitive. These symptoms are usually called postpartum blues. The still high rate of postpartum blues in the world, namely 70-80%, and the rate of postpartum blues in Indonesia, namely 60-70%, shows that the mental health problems of postpartum mothers require special attention. The results of a preliminary study at the Mrican Community Health Center, Kediri City, showed that 70% of 52 postpartum mothers (36 respondents) experienced anxiety during the postpartum period. In Indonesia, postpartum blues is still considered normal and does not require special treatment, even though this problem has a high impact on the welfare of postpartum mothers and their babies.Objectives: The aim of this research is to determine the effectiveness of the Nareswari method (Breathing, Relaxation, and Coloring) in reducing the anxiety level of postpartum mothers as an effort to prevent cases of postpartum blues. The Nareswari method is a combination of hypnobreastfeeding techniques and coloring therapy (coloring).Methods: This type of research is observational analytical experimental research with a case-control approach with two group pretest and post-test. The independent variables are hypnobreastfeeding and coloring hypnosis. The dependent variable is the level of anxiety of postpartum mothers and the number of samples in this study was 50 respondents.Results: The results of statistical tests show a significant difference between the level of anxiety in the treatment group and the control group (p-value = 0.0000 < α value 0.05).Conclusions: The Nareswari method is effective in reducing anxiety levels in postpartum mothers. There was a significant reduction in anxiety levels after postpartum mothers routinely used this method for one month.